Spatial variation of human development indicators in Saudi Arabia - Ahmed, Mohammed bin Ibrahim Ramadan; Al Moallem, Zohor Bint Omar Abdullah (Journal of Economic, Administrative and Legal Sciences, 2017)
This study is concerned about the human development in Saudi Arabia from a geographical perspective. It focused on analyzing and explaining the spatial variation of human development indicators on the level of the administration areas of the kingdom. It classified the indicators developmentally according to the value of human development indexes. Further، the study attempted to evaluate the core dimensions included in the human development indexes – health، knowledge and appropriate standard of living – showing their points of strength and weakness. To achieve the objectives of this study، some statistical methods have been used، e.g. Cluster Analysis and Moran’s Index. The study revealed that human development is randomly distributed over the administration areas of the kingdom of Saudi Arabia. Further the quantitative analysis revealed that the dimension of standard of living is the most diversified and varied factor of Human development over the administrative areas of Saudi Arabia. In addition، cluster analysis showed five geographical patterns for human development: very high human development pattern in AL-Riyadh and Makkah Al-Mokarramah areas، with very high standard of living and knowledge، high human development represented in Al Madinah Al-Monawarah، The Eastern Region، Aseer with high health dimension of human development، medium human development pattern represented in Qaseem، Tabuk، Hail، Najran، Al-Baha and Al-Jouf which showed lower living conditions in these areas، low human development pattern in The Northern Borders in which all dimensions are low، and very low human development pattern in Jazan area where all indicators are very low. Based on the result achieved the study proposed some remedial solutions for these problems, which are as follows: work towards integration of health system in all kingdom areas, develop the system of higher education to building a knowledgeable society, enhance the standard of living for all community members, and focus on achieving very high human development in all parts of the Kingdom administrative areas.